Correlation of Serum levels of Chromium, Copper, and Manganese with the Glucose levels in Type 2 Diabetes Mellitus in Iraq - Khameed, Ahmed Z.; Al-Yassin, Hedef D. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The metabolism of many trace elements, such as chromium, copper, and manganese, was reported to be altered in type 2 diabetes mellitus. This element may have specific roles in the pathogenesis and progress of this disease.Objectives: To evaluate the serum levels of copper, chromium, and manganese in type 2 diabetic patients in Iraq. Methods: This case-control study included 100 type 2 diabetic patients, 35-60 years old, with high BMI as cases, and 100 non-diabetic subjects as controls who were healthy volunteers not suffering from type 2 diabetes (staff and students). The data was collected from October 2022 until January 2023. The cases were seen in the Diabetes Consultation Unit at Baghdad Teaching Hospital, Medical City. Serum chromium, copper, and manganese were measured using atomic absorption. ELISA was used to test for insulin. spectrophotometry to measure glucose and HPLC was used to measure whole-blood HbA1c. Insulin resistance was calculated using the semi-empirical formula: HOMA-IR = glucose * insulin / 405 (glucose in mg/dl). To test for the difference between means of numerical data across several parameters, ANOVA tests were utilized. Pearson’s. correlation was used to test the correlation between variables.Results: Diabetics had higher HbA1c, serum copper, and blood glucose than healthy controls. Compared to controls, diabetics had lower serum chromium and manganese (P value < 0.01). In diabetics, chromium and manganese are highly negatively correlated with insulin resistance. Copper levels increase with increasing insulin resistance. Insulin levels were greater in type 2 diabetics (18.6 ± 4.1 mlU/L) than in the control (6.2 ± 1.3).Conclusions: Serum copper was high while serum chromium and manganese were low in type 2 diabetics. which indicates that these elements may have a role in the occurrence and development of type 2 diabetes.